Activate: Randomized Clinical Trial of BCG Vaccination against Infection in the Elderly - Giamarellos-Bourboulis, Evangelos J; Tsilika, Maria; Moorlag, Simone; Antonakos, Nikolaos; Kotsaki, Antigone; Domínguez-Andrés, Jorge; Kyriazopoulou, Evdoxia; Gkavogianni, Theologia; Adami, Maria-Evangelia; Damoraki, Georgia; Koufargyris, Panagiotis; Karageorgos, Athanassios; et al. (Cell, 2020)
BCG vaccination in children protects against heterologous infections and improves survival independently of tuberculosis prevention. The phase III ACTIVATE trial assessed whether BCG has similar effects in the elderly. In this double-blind, randomized trial, elderly patients (n = 198) received BCG or placebo vaccine at hospital discharge and were followed for 12 months for new infections. At interim analysis, BCG vaccination significantly increased the time to first infection (median 16 weeks compared to 11 weeks after placebo). The incidence of new infections was 42.3% (95% CIs 31.9%-53.4%) after placebo vaccination and 25.0% (95% CIs 16.4%-36.1%) after BCG vaccination; most of the protection was against respiratory tract infections of probable viral origin (hazard ratio 0.21, p = 0.013). No difference in the frequency of adverse effects was found. Data show that BCG vaccination is safe and can protect the elderly against infections. Larger studies are needed to assess protection against respiratory infections, including COVID-19 (ClinicalTrials.gov NCT03296423).